The use of wetlands for effluent polishing at Placer Dome, Campbell Mine - Benoit Bissonnette; David Gelderland (Canadian Institute of Mining, Metallurgy and Petroleum, 2003)
"The Campbell Mine Constructed Wetlands has been in full operation, processing effluent from the water treatment plant of the mill circuit for the last two years.The overall results are extremely positive with dramatic improvements for the originally targeted parameters – Ammonia, Copper and toxicity.• Ammonia concentrations were reduced from an average of 5 mg/L to an average of 0.43 mg/L which translates to an average reduction of 91%.• Copper concentrations were reduced from an average concentration of 0.054 mg/L to an average of 0.019 mg/L, which translates to an average reduction of 65%.• LC50 Acute toxicity testing revealed no impact.• IC25 Chronic toxicity tests revealed no impairment to growth or reproduction.As a result of the improvements in discharge water quality from the wetland, 100 percent compliance with respect to all Certificate of Approval, MISA and MMER regulations for effluent will be consistently achieved.The system has proven to be very easy to operate and maintain, with a minimum of care. Given some basic rules are followed, the construction of the wetlands was straightforward and relatively inexpensive compared to other treatment methods.The ecological benefits of the operation of the wetland are also quite substantial, as is the positive image of the corporation in environmental stewardship.INTRODUCTIONOver the last four years, Campbell Mine has adopted an aggressive schedule for the development of wetlands for use as the final stage of effluent treatment within the tailings management facility. The focus of this work has been to utilize natural biological systems to provide Campbell Mine with a 100 percent compliant water quality with respect to all MISA, MMER and COA discharge criteria at all times throughout the effluent discharge period."